The A-kinase anchoring protein (AKAP)-Lbc-signaling complex mediates α1 adrenergic receptor-induced cardiomyocyte hypertrophy - Appert-Collin, Aline (National Academy of Sciences, 2007)
In response to various pathological stresses, the heart undergoes a pathological remodeling process that is associated with cardiomyocyte hypertrophy. Because cardiac hypertrophy can progress to heart failure, a major cause of lethality worldwide, the intracellular signaling pathways that control cardiomyocyte growth have been the subject of intensive investigation. It has been known for more than a decade that the small molecular weight GTPase RhoA is involved in the signaling pathways leading to cardiomyocyte hypertrophy. Although some of the hypertrophic pathways activated by RhoA have now been identified, the identity of the exchange factors that modulate its activity in cardiomyocytes is currently unknown. In this study, we show that AKAP-Lbc, an A-kinase anchoring protein (AKAP) with an intrinsic Rho-specific guanine nucleotide exchange factor activity, is critical for activating RhoA and transducing hypertrophic signals downstream of α1-adrenergic receptors (ARs). In particular, our results indicate that suppression of AKAP-Lbc expression by infecting rat neonatal ventricular cardiomyocytes with lentiviruses encoding AKAP-Lbc-specific short hairpin RNAs strongly reduces both α1-AR-mediated RhoA activation and hypertrophic responses. Interestingly, α1-ARs promote AKAP-Lbc activation via a pathway that requires the α subunit of the heterotrimeric G protein G12. These findings identify AKAP-Lbc as the first Rho-guanine nucleotide exchange factor (GEF) involved in the signaling pathways leading to cardiomyocytes hypertrophy.